Teachers' Self-efficacy and Their Implementation of Instructional Best Practices - Wilmer, Measha (East Carolina University)
Bray-Clark and Bates (2003) asserted that teaching is a demanding job with unpredictable challenges which means that teachers' ability to be effective is partly dependent on their perceived self-efficacy. When teachers perceive their self-efficacy as waning, this may affect their commitment to their job and their willingness to implement instructional best practices. This poses a challenge for teachers' level of motivation and students' academic success as every student deserves quality instruction. The purpose of my study was to explore and alleviate a problem of practice regarding teachers' self-efficacy and their implementation of instructional best practices. The participants in my study were teachers who worked at a rural middle school in the North Central area of North Carolina. They volunteered to participate in my study after being given detailed information about the procedures and ethical considerations. I used a parallel convergent mixed methods research design which means I collected and analyzed both qualitative and quantitative data at the same time. As a trained mentor, I implemented a mentorship and support initiative where I worked with participants to improve their instructional best practices and by extension, their self-efficacy. I administered the Tschannen-Moran and Hoy (2001) Teacher Sense of Self-efficacy scale (TSES) to determine teachers' perception of their self-efficacy. While the data from the TSES were being analyzed, I conducted classroom observations over 2 weeks followed by post observation conferencing. I used the data from my classroom observations to inform my planning with participants for future lessons. Following my intervention, I made weekly visits to participants' classes to observe their implementation of instructional best practices then conducted post observation interviews to learn more about their self-efficacy. I used the results to determine that associations could be made between teachers' self-efficacy and their implementation of instructional best practices.
Keywords: Teacher self-efficacy; instructional best practices; school culture; professional development; culturally responsive teaching; Middle school teachers--In-service training--North Carolina; Teacher effectiveness--North Carolina; Mentoring in education--North Carolina; Academic achievement; Rural schools--North Carolina